2014
DOI: 10.1371/journal.pone.0108060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-17A on the Migration and Invasion of NPC Cells and Related Mechanisms

Abstract: In carcinogenesis, inflammasomes may play contradictory roles through facilitating anti-tumor immunity or inducing oncogenic factors. Their function in cancer remains poorly characterized. In this study, we explored the effect of interleukin-17A (IL-17A) on the migration and invasion activity of nasopharyngeal carcinoma (NPC) cell lines and account for related mechanisms. Our results revealed that exogenous IL-17A promoted cell migration and invasion significantly in both NPC-039 and CNE-2Z cell lines. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
2
14
1
Order By: Relevance
“…19 In two human nasopharyngeal cancer cell lines, IL-17 induces expression of MMP2 and MMP9 through activation of p38 kinase and NF-κB pathways, which is accompanied with decreased full-length E-cadherin and increased vimentin levels. 52 It is not clear whether MMP2 and MMP9 expression plays any role in regulating E-cadherin and vimentin levels in that study. 52 Nevertheless, our present study clearly shows that MMP7 cleaves E-cadherin into sE-cadherin in both human prostate cancer cell lines and mouse prostate tumors, resulting in disruption of E-cadherin-β-catenin complex and release of β-catenin that activates the downstream EMT transcription factors.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…19 In two human nasopharyngeal cancer cell lines, IL-17 induces expression of MMP2 and MMP9 through activation of p38 kinase and NF-κB pathways, which is accompanied with decreased full-length E-cadherin and increased vimentin levels. 52 It is not clear whether MMP2 and MMP9 expression plays any role in regulating E-cadherin and vimentin levels in that study. 52 Nevertheless, our present study clearly shows that MMP7 cleaves E-cadherin into sE-cadherin in both human prostate cancer cell lines and mouse prostate tumors, resulting in disruption of E-cadherin-β-catenin complex and release of β-catenin that activates the downstream EMT transcription factors.…”
Section: Discussionmentioning
confidence: 75%
“…52 It is not clear whether MMP2 and MMP9 expression plays any role in regulating E-cadherin and vimentin levels in that study. 52 Nevertheless, our present study clearly shows that MMP7 cleaves E-cadherin into sE-cadherin in both human prostate cancer cell lines and mouse prostate tumors, resulting in disruption of E-cadherin-β-catenin complex and release of β-catenin that activates the downstream EMT transcription factors. Loss of membrane-associated E-cadherin has been shown to trigger β-catenin nuclear localization with subsequent c-Myc expression and cellular proliferation in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 75%
“…Worth mentioning is the fact that ZEB1, an essential transcription factor, could facilitate metastasis of cancer cells to promote EMT [39], including in cervical cancer [40]. Moreover, SB203580 was also reported to lead to reduced EMT and decreased invasion of NPC-039 and CNE-2Z cell lines [41], highlighting an important point that inhibiting ZEB1-AS1 expression and blocking p38MAPK signaling pathway could significantly suppress the EMT process in cancer cells. Last but not least, the co-existence of Anisomycin and ZEB1-AS1 siRNA could increase EMT formation, as compared with ZEB1-AS1 siRNA alone, which suggested that ZEB1-AS1 siRNA may reduce metastasis and EMT of Hela cells by blocking the p38MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported that IL‐17 induced EMT via Stat3 in lung adenocarcinoma and enhanced lung cancer cell migration through activating NF‐κB by upregulating ZEB1 expression . IL‐17 promotes nasopharyngeal carcinoma cell migration and invasion by regulation of the expression of MMP‐2/‐9 and EMT via the p38‐NF‐κB signaling pathway . Tumor hypoxia with deregulated expression of HIF leads to poor prognosis of patients diagnosed with solid tumors .…”
Section: Discussionmentioning
confidence: 99%